Analisis Tindak Tutur Ilokusi dalam Lirik Lagu Hati-hati di Jalan Karya Tulus - Anindira Rahma Kautsarani; Farida Yufarlina Rosita; Berlian Pancarrani (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to analyze the types of illocutional speech acts contained in the lyrics of the song Hati-Hati di Jalan karya Tulus. The background of this research is based on the importance of understanding song lyrics as a form of communication that is full of pragmatic meaning, especially in the context of emotions and interpersonal relationships. The method used is qualitative descriptive with a content analysis technique based on the theory of classification of illocutional speech acts by Searle. Data were taken from all song lyrics and analyzed based on five types of illocution speech acts, namely representative, directive, expressive, commissive, and declarative. The results of the study show that in the lyrics of this song there are four types of illocutional speech acts, namely representative, directive, expressive, and commissive, with a dominance of representative and expressive types. The act of speech reflects various communication functions such as expressing beliefs, expressing feelings, giving hope, and showing commitment. This research implies that song lyrics can be a valuable object of pragmatic study, as well as enriching the understanding of communication strategies through language in popular literary works. This study has limitations on the scope of a single song and the interpretation of the researcher, so it is recommended that the next study examine other songs to broaden the perspective.